Cardiovascular abnormalities in multisystem inflammatory syndrome in children related to COVID-19 - Bravo-Valenzuela, Nathalie Jeanne Magioli; Panizzi, Thiago Taucei; de Souza, Katharine Aguiar; Stutz, Gabriela Blanco; Aurelio, Rafaela Vieira Meirelles; Rodrigues, Marta Cristine Felix; de Almeida, Rozana Gasparello; Lemos, Fernanda Maria Correia Ferreira; Araújo, Alan de Lima; Sztajnbok, Flavio Roberto; Fonseca, Adriana Rodrigues (Frontiers in Pediatrics, 2026)
IntroductionThe COVID-19 pandemic began with the identification of SARS-CoV-2 in December 2019. Although children usually have milder acute symptoms, they can develop severe systemic symptoms termed pediatric multisystem inflammatory syndrome (MIS-C). This study reviews research in children and adolescents diagnosed with MIS-C, focusing on cardiovascular abnormalities.MethodologyThis systematic review was conducted following PRISMA guidelines. The review protocol was prospectively registered in the Prospective Register of Systematic Reviews (PROSPERO; registration number: CDR420251232497). A search strategy was constructed to identify the studies focusing on cardiovascular abnormalities in children and adolescents with MIS-C published in Portuguese and English at PubMed and Scielo from January 2020 to February 2025. The eligibility criteria and data extraction strategy were guided by the PICO framework.ConclusionsMyocardial dysfunction and coronary abnormalities are the most frequent cardiovascular features in patients with MIS-C. Strain technology in echocardiography identifies early myocardial dysfunction, with studies showing persistent subclinical injuries. Despite ejection fraction and coronary anomalies returning to normal short to medium term, long-term cardiovascular effects of MIS-C remain uncertain, necessitating ongoing cardiology monitoring.